Impact of Using Augmented Reality on Students' Cognitive And Affective Aspects In Terms of Education Level - Runisah Runisah; Sudirman Sudirman; Muhamad Galang Isnawan; Farid Gunadi; Rosyadi Rosyadi; Aloisius Loka Son; Lily Aulin Assya (International Journal of Science Education and Cultural Studies, 2022)
Many studies related to the use of Augmented Reality (AR) in the learning process. However, not many researchers have studied the effect of using AR on affective and cognitive aspects in terms of education level. To uncover this problem, the researcher uses a systematic literature review (SLR) design. In this study, the SLR stage consisted of four stages (1) problem formulation; (2) literature search; (3) identification of the type of research; (4) information retrieval. The findings of this study reveal that the use of AR technology has an effect on cognitive and affective aspects at the elementary and high school education levels. Middle school is the level of education that mostly applies AR technology. This study provides a recommendation that AR technology can be a medium for learning mathematics that can be applied by teachers and students at the primary and secondary education levels.